2011
DOI: 10.1088/0957-0233/22/12/125703
|View full text |Cite
|
Sign up to set email alerts
|

The use of the PeakForceTMquantitative nanomechanical mapping AFM-based method for high-resolution Young's modulus measurement of polymers

Abstract: SUMMARYPeakForce TM Quantitative Nanomechanical Mapping (QNM TM ) is a new atomic force microscopy technique for measuring the Young's modulus of materials with high spatial resolution and surface sensitivity, by probing at the nanoscale. In the present work, modulus results from PeakForce™ QNM™ using three different probes are presented for a number of different polymers with a range of Young's moduli that were measured independently by Instrumented (nano) Indentation Testing (IIT). The results from the diamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
204
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(213 citation statements)
references
References 17 publications
4
204
0
5
Order By: Relevance
“…The absorbed electron energy within the PDMS at the sub-surface rigidity gradient is determined by two factors: (i) the incident electron energy (30 keV in this study); and (ii) the scattering of electrons within the elastomer, which depends on the density of the material (schematised in Figure 1A). Analysis of Monte Carlo simulations [27] indicated that over 90% of the e-beam energy was absorbed within approximately the top 3 µm of the PDMS (Figure 1B), resulting in a columnar scattering profile with a broad spreading base that diminished in intensity with increasing depth. Lateral scattering within the top layer was confined to ~ 30 nm at 30 keV.…”
Section: Modulation Of Pdms Rigiditymentioning
confidence: 99%
See 2 more Smart Citations
“…The absorbed electron energy within the PDMS at the sub-surface rigidity gradient is determined by two factors: (i) the incident electron energy (30 keV in this study); and (ii) the scattering of electrons within the elastomer, which depends on the density of the material (schematised in Figure 1A). Analysis of Monte Carlo simulations [27] indicated that over 90% of the e-beam energy was absorbed within approximately the top 3 µm of the PDMS (Figure 1B), resulting in a columnar scattering profile with a broad spreading base that diminished in intensity with increasing depth. Lateral scattering within the top layer was confined to ~ 30 nm at 30 keV.…”
Section: Modulation Of Pdms Rigiditymentioning
confidence: 99%
“…Samples with known elastic moduli were used to validate the tip calibration process (low-density polyethylene 10 MPa and 14 MPa and PDMS 1 MPa). [27] The analysis of the Derjaguin-Mueller-Toporov (DMT) modulus was performed via Nanoscope Analysis software. As mentioned above, the Monte Carlo simulations indicate that most of the electron energy is deposited in a ~ 3 µm thick layer at the surface of the PDMS film.…”
Section: Modulation Of Pdms Rigiditymentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, several methods have been proposed to complement the high spatial resolution of the force microscope with quantitative information about the mechanical properties of the interface [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] . In fact, the goal of combining topography with compositional contrast can be traced back to the origin of dynamic AFM with the development of phase-imaging AFM.…”
mentioning
confidence: 99%
“…The suitability of the elastic unloading analysis for polymeric materials that show pronounced viscoelastic behaviour has been questioned for the same reasons. Nevertheless, a similar approach to that recommended above for metals has recently been applied to a range of commercial polymers by Young and co-workers at NPL [12]. The elastic modulus measurements showed reasonably good agreement with supplier quoted values (presumably from bulk methods) and a new atomic force microscopy technique using Hertzian contact mechanics.…”
Section: The International Standard For Depth-sensing Indentation -Ismentioning
confidence: 53%